Landscapes of an ideal COVID-19 vaccine - Ghimire, Tirth Raj (Applied Science and Technology Annals, 2020)
This paper discusses the designing strategies for an ideal COVID-19 vaccine. It gives an illustrative methodology of a complete immunologic understanding of an ideal vaccine that can be used to formulate and prepare a COVID-19 vaccine antigen.